The role of implementing meditation in buddhist sunday school student character development at wisma meditation vipassana bodhi ratana Jepara central Java - I ketut Damana (Institute of Computer Science (IOCS), 2023)
The purpose of the teacher is to program the formation of character in Buddhist Sunday schools because the teacher is not yet perfect in forming non-formal character education. The finding of the teacher teaching in the implementation of meditation is because the teacher has difficulty assessing the character of the meditation students. Therefore the teacher is limited to playing an active role in programming student meditation that is relevant to modern life. This study used a qualitative approach focused on sitting, standing, walking and waking meditation. This research involved contributions from meditation teacher monks in Jepara. Data were collected by observation, interview, and documentation study techniques. The solution proposed in this study found that the role of implementing meditation on the formation of student character was in the factor of teacher readiness to teach at Buddhist Sunday schools. Obstacles in implementing meditation that occur become the most important problem in character building. The results of the discussion of this study show that the findings are on the formation of vipassana character and the formation of samatha character. The conclusion of the research on the inhalation and exhalation of breath as a character object for students to meditate.